(untitled) (South East Asia Journal of Public Health, 2016)
The occupational health and safety service is still in the developing stage. In Bangladesh, this service is merely focused on welfare for the garments workers. Statistics on musculoskeletal symptoms prevalence and risk factors analysis for any occupational group can assist to develop ergonomic based prevention and intervention programs. However, there is no information available about the musculoskeletal symptoms prevalence amongst automobile mechanics in Bangladesh. The aim of study is to estimate the prevalence of musculoskeletal symptoms and reveal association with physical risk factors among automobile mechanics. This cross-sectional study was performed with 100 automobile workers conveniently selected from different automobile workshop of Dhaka Division (Savar and Gabtoli) of Bangladesh. The short version of Dutch Musculoskeletal Questionnaire was used to determine the prevalence and associated physical risk factors. Furthermore, the Rapid Entire Body Assessment was used to identify the physical risk level of musculoskeletal symptoms. The prevalence of musculoskeletal symptoms during the last 12 months preceding data collection was reported at 77%. The most affected body parts were lower back (67%) then the hip (53%). Socio-demographic and physical risk factors were significantly (p<0.05) associated with reported musculo-skeletal symptoms. It is highly concerning issue for employing occupational health and safety program for those workers. South East Asia Journal of Public Health Vol.6(1) 2016: 8-13